Study of the reproducibility of the 2004 World Health Organization classification of urothelial neoplasms - Pallavi Sharma; Hema Kini; Radha R Pai; Kaushalya K Sahu; Jyoti Kini (Wolters Kluwer Medknow Publications, 2015)
The aim of the study was to evaluate urinary bladder biopsies showing papillary urothelial neoplastic lesions based on the 2004 WHO/ISUP classification of Urothelial Neoplasms of the Urinary Bladder, to assess the reproducibility of the bladder carcinoma grade. Fifty consecutive transurethral tumor resection biopsies were evaluated by four pathologists independently. The final diagnoses of each pathologist were subjected to statistical analysis to assess the degree of interobserver variability and reproducibility of this classification. Significant interobserver variation was found in the reporting of urothelial neoplasms. In 22 instances there was difference in opinion between PUNLMP and low-grade carcinoma, and in 59 instances between low and high grade carcinoma. The 4 observers never unanimously agreed on the diagnosis of PUNLMP.